PEMANFAATAN MEDIA ORIGAMI BERBASIS TEMA DI PAUD PGRI LASIRIBADA KEL. KAMBOWA - Mirmawan, Sofa; Henny, Henny; Hartati, Hartati (SINERGI : Jurnal Riset Ilmiah, 2025)
The study was motivated by the limited availability of learning media, as several existing materials were damaged and incomplete due to prolonged use. As a result, children were less enthusiastic during learning activities. This research aims to explore the utilization of theme-based origami media in early childhood education. Origami media was employed to enhance children's learning interest, creativity, and fine motor skills through thematic activities. The research method used was Participatory Action Research (PAR) with a descriptive qualitative approach. The subjects of the study were 10 children from Group B, aged 5–6 years. Data collection techniques included observation, interviews, and documentation. The findings showed that the use of theme-based origami media was effective in increasing children's engagement in learning. Children showed enthusiasm, understood the learning material, and actively participated in the process through themes such as Plants, Sea Transportation, Printed Communication, and My Country. In conclusion, theme-based origami media can serve as a creative, enjoyable, and meaningful alternative for early childhood education.